Cu1-xSrxTiO3 thin film resistors for Carbon Monoxide sens-ing (International Journal of Food and Nutritional Sciences, 2022)
Thin films of pure and CuO-modified SrTiO3 (STO) were prepared by spray pyrolysis technique. The Cu1-xSrxTiO3; Cu 0.1weight% thin films were prepared by spraying aqueous solution Sr (Cl2)6H2O, TiCl3 and CuCl2 precursors. Prepared films were fired at 500o C for 30 min. The Cu1-xSrxTiO3(x=0.1 to 0.9) thin films were prepared by spray pyrolysis method. From XRD profiles, effect of Cu concentration on the crystal structure, average particle size and lattice parameter were investigated. The gas sensing properties of pure and CuO modified STO thin films were investigated for various gases on homemade static gas sensing system. The maximum gas re-sponse (2000) was obtained for CuO doped STO thin films. The CuO modification has signifi-cant effect on sensing performance. The instant response T25 and fast recovery T45 are main fea-tures of sensor. The structural properties of the films were estimated using X-ray diffraction study. The particle properties were analyzed by FE-SEM and EDS analysis. Selectivity, response and recovery times were investigated and discussed.